Sistem pengelolaan nilai rapor menggunakan aplikasi microsoft excel berbasis VBA (visual basic for application) di SMKN 1 Palasah - Mahpudin, Asep; Latif Setiawan, Dena; Kartika, Idha (Jurnal Sains Indonesia, 2021)
Report Value Management System Using Microsoft Excel Application based on VBA (Visual Basic for Applications) at SMKN 1 Palasah. This study aims to: (1) Know the report card value management system using Microsoft Excel based on VBA (Visual Basic for Applications) at SMKN 1 Palasah; (2) Know the quality of the report card value management system software using Microsoft Excel-based on VBA (Visual Basic for Applications). ) at SMKN 1 Palasah based on functionality and usability in software quality testing. The research was conducted using the Research and Development (R&D) method, using the Waterfall Model development model. Product testing is based on the objectives to be achieved focuses on testing aspects of functionality and usability. The results obtained in this study are: (1) The research produces an information system for managing report cards using a Microsoft Excel application based on VBA (Visual Basic for Applications), making it easier for homeroom teachers to process student reports cards; (2) The calculation results show that the report card value management system is included in the "Success" criteria in the functionality test, and the usability calculation results get 91.9%, so that it is included in the very feasible category. It can be concluded that the developed student report card processing information system is easy to use and valuable for users so that the research objectives are achieved.